Alexander Kondratiev’s letters to Valery Bryusov (conclusion) - Nikolay Bogomolov (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2019)
For the first time all Alexander Alexeevich Kondratiev's letters to Valery Bryusov are published. A reflection of relationships between two poets, they are far more valuable, representing a very rich material on the history of Russian modernism in general. Persons and literary events mentioned are provided with extensive comments which incorporate these documents into the cultural context of the epoch. Considering the absenсe of response letters (which are presumably lost with the rest of Kondratiev's papers), these letters are of paramount importance for the reconstruction of Bryusov's biography.